Communal erfahrung and metropolitan erlebenis: the prelude, by William Wordsworth, through the lens of Walter Benjamin - de Aguiar, Angiuli Copetti (2020)
In his autobiographical poem The Prelude, the English poet William Wordsworth strives to find in his memory the events that gave shape to his subjective life and to reassess his experiences through the lens of his present consciousness. In this essay, we intended to analyze the types of experience described by Wordsworth and the relationship they hold with the environment which gave them birth. With this purpose we employed Walter Benjamin’s concepts of ‘erfahrung’, ‘erlebnis’ and ‘shock’, and analyzed excerpts from The Prelude through these categories. We observed that experiences of erfahrung are found especially in Wordsworth’s childhood in the countryside, amidst his little rural community. Experiences of erlebnis take place in the narrative as backgrounds against which erfahrung experiences are shown more clearly, especially in the contrast between urban and rural life. Shocks, on the other hand, appear as moments impressed on the memory by their singularity and ineffability, and which haunt the poet still years later without ever fully disclosing their meaning. We concluded that in The Prelude, the countryside and the community are the locus of living erfahrung experiences while the city offers only erlebnis to the subject, although, for the poet, moments of shock can rescue from the erlebnis flashes of authentic experience.